Karakter bilateral simetri ikan betutu (Oxyeleotris sp.): Kajian keragaman morfologi sebagai dasar pengembangan budidaya - Muhammad Nadjmi Abulias; Dian Bhagawati (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. Genetic diversity information of Gobiidae is needed as a basis for management of its culture or conservation efforts. Mean while, the stability development of the paired organs in animals is closely related to the level of their genetic diversity. In this regard, a study has been conducted to determine of bilateral symmetry characteristics of marble gobies from Jenderal Soedirman reservoir of Banjarnegara and Rawapening Swamp of Salatiga. A survey method was used with purposive sampling technique. The observed variables were abnormalities and meristic bilateral characters. The characters including the number of soft rays on pectoral fins and pelvic fins, and the number of scales on lateral lines. The results showed that both marble gobies from Jenderal Soedirman Reservoir and Rawapening Swamp did not show abnormalities. However, their bilateral meristic characters had been fluctuated, especially for pectoral fins and lateral lines; whereas pelvic fins seem to be symmetry. According to their observed bilateral symmetry characters, in general, it could be concluded that marble gobies from Jenderal Soedirman Reservoir had a better genetic diversity compare to those from Rawapening Swamp. Therefore, it can be used as local genetic resources.Key words. Bilateral symmetry character, marbel gobies, Jenderal Soedirman Reservoirs, Rawa pening Swamp